Factors Affecting Traditional Culinary MSMEs in Denpasar City: A Case Study Of Ayam Betutu - Ni Kadek Gita Mahardani; Surya Dewi Rustariyuni (International Journal of Economics, Management and Accounting, 2025)
MSMEs (Micro, Small, and Medium Enterprises) are one of the main drivers of Indonesia’s economy. However, many MSMEs still face limited access to financing. One traditional Balinese culinary product that attracts tourists is ayam betutu, which represents the MSME sector. This study aims to analyze the influence of own capital, business duration, working hours, and e-commerce on the income of ayam betutu culinary MSMEs in Denpasar City, both simultaneously and partially. This research employs a quantitative method using multiple linear regression analysis. The sample was determined using purposive sampling, with criteria including MSMEs engaged in traditional culinary businesses with ayam betutu as their main product and those that utilize e-commerce in their business operations. A total of 70 ayam betutu culinary MSME actors in Denpasar City were included. The findings reveal that, simultaneously, own capital, business duration, working hours, and e-commerce have a significant effect on MSME income. Partially, own capital, business duration, and e-commerce have a positive and significant effect on income, whereas working hours do not have a significant partial effect. The implication of this study is that MSME actors need to improve their capacity in capital management, maintain business continuity, and optimize e-commerce utilization to increase income. The government is expected to support MSMEs through financial and digital literacy training, institutional strengthening, and the facilitation of mentoring programs and sustainable access to financing.